1960
DOI: 10.1103/physrevlett.5.276
|View full text |Cite
|
Sign up to set email alerts
|

Deuteron Production in High-Energy Collisions

Abstract: Pyatt, Jr., Phys. Rev. (to be published). A similar designation for n-p fits with YLAN as the first four letters has been partly described in G. Breit, M. H. Hull, Jr., K. Lassila, and K. D. Pyatt, Jr., Phys. Rev. Letters 4, 79 (1960). 3 Fit YLAN3 is a development on fit YLAN2M with a major difference regarding the sign of pj through most of the energy range. It includes among other matters the employment of an improved mass treatment for the OPEP as described in the last reference of reference 2 and differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1961
1961
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…These experiments dealt with forward kinematic regions, where composite nuclei could not have originated from multifragmen- tation of an excited target spectator. One such model, proposed by Dmitrii Blokhintsev [35], attributed an important role to density fluctuations in the target nucleus, while Rolf Hagedorn proposed a statistical approach in which a deuteron could be directly produced in an elementary nucleon-nucleon interaction [36]. Hagedorn subsequently employed this model to calculate the rate of antideuteron production in p-nucleus interactions [37], but the resulting prediction differed greatly from the observations of Dorfan et al [26], namely, the prediction exceeded the measured rate of antideuteron production by a factor of about 2 × 10 3 .…”
Section: Early Experimental Discoveries Of Antinuclei At Proton Accelmentioning
confidence: 99%
“…These experiments dealt with forward kinematic regions, where composite nuclei could not have originated from multifragmen- tation of an excited target spectator. One such model, proposed by Dmitrii Blokhintsev [35], attributed an important role to density fluctuations in the target nucleus, while Rolf Hagedorn proposed a statistical approach in which a deuteron could be directly produced in an elementary nucleon-nucleon interaction [36]. Hagedorn subsequently employed this model to calculate the rate of antideuteron production in p-nucleus interactions [37], but the resulting prediction differed greatly from the observations of Dorfan et al [26], namely, the prediction exceeded the measured rate of antideuteron production by a factor of about 2 × 10 3 .…”
Section: Early Experimental Discoveries Of Antinuclei At Proton Accelmentioning
confidence: 99%
“…That is to say, most of the effect can be accounted for by the finite probability of two outgoing high-energy nucleons having small enough relative momenta to fit the deuteron wave function. 13 Whether these are produced on quasifree nucleon-nucleon collisions 6 or in a nucleonic cascade, 7 one can use the observed nucleon momentum distribution emerging from proton-beryllium (say) collisions to compute the overlap of two such particles to form an outgoing deuteron. The same considerations should then be valid for d production if we assume that the antinucleons are produced independently in 30-BeV collisions.…”
mentioning
confidence: 99%
“…= ^F(ri2)I(rip+T2p) (10) will lead to an energy difference between a proton and a neutron in the state v given by the expression…”
Section: + (E A~ec Y+[t C^e A) /Iymentioning
confidence: 99%
“…In another process Hagedorn [10][11][12] suggested that statistical nucleon-nucleon interactions at high energies might yield sufficient deuterons to explain the anomaly. The reaction occurring would be of the type />+ nucleon-»d+pions+ others.…”
Section: Introductionmentioning
confidence: 97%